Geology drives the spatial patterning and structure of termite mounds in an African savanna. Issue 3 (13th March 2018) - Muvengwi, Justice; Davies, Andrew B.; Parrini, Francesca; Witkowski, Edward T. F.
Abstract: Termite mounds perform important roles in savanna ecosystems, generating heterogeneity and influencing ecosystem processes across multiple trophic levels. However, the influence the environment and neighboring termite colonies have on mound spatial patterning and structure is poorly understood, despite the profound implications such dynamics can have on ecosystems. To better understand these drivers, we mapped the spatial distribution and size of active and inactive Macrotermes mounds in eight 1‐km 2 plots on contrasting geologies, nutrient‐rich granite and nutrient‐poor basalt, in a semi‐arid Zimbabwean savanna. Although mound density was not significantly different between basalt (5.5 mounds/ha) and granite (6.1 mounds/ha), termite mound structural attributes and spatial distribution patterns varied greatly between geologies. Mound size distributions differed between the geologies and mounds were 2.6 times taller and 3.9 times wider and had 15 times greater lateral surface area on granite. Subsequently, 6% of the total landscape was covered by mounds on granite compared with only 0.4% on basalt. On granite, large mounds exhibited significant over‐dispersion at scales below 30 m, signifying density‐dependent thinning. Furthermore, small mounds were clustered around large mounds, likely a result of the budding of new colonies comprising fully fledged castes less vulnerable to competition. In contrast, random patterning was evident on comparably homogenous basalt. Our results demonstrate the powerful influence geological substrate has on mound spatial patterning and structure, suggesting that the importance of termite mounds for ecosystem functioning is more pronounced on nutrient‐poor granitic substrates than basalts because of the pronounced over‐dispersion, which maximizes mound production per unit area, and much larger mound sizes here.